COVID-19 vaccine hesitancy among adults in Hawassa City Administration, Sidama Region, Ethiopia: A community-based study - Yohannes, Seblewongel; Alemayehu, Akalewold; Woldesenbet, Yohannes Markos; Tadele, Temesgen; Dangiso, Desta; Birhanu, Muntasha; Woldesemayat, Endrias Markos (Frontiers in Public Health, 2023)
Objective: COVID-19 vaccine is one of the key measures to control the disease COVID-19. However, some people are hesitant to take the vaccine. The objective of this study was to assess COVID-19 vaccine hesitancy and associated factors among adults in Hawassa City Administration, South Ethiopia. Method: From March 1 to 30, 2022, we conducted a community-based cross-sectional study among randomly selected 622 adults in Hawassa City Administration. A multi-stage sampling technique was used to recruit the study participants. Data were collected by four trained high school completed students through a pretested structured questionnaire. Data entry and analysis were done using SPSS version 20 statistical package. Descriptive statistics and logistic regression analysis were done. Statistically significant associations were reported at P-value < 0.05. Result: There was high level of good knowledge of COVID-19 vaccine, 400 (64.3%) and positive attitude towards COVID-19 vaccine, 425 (68.3%) among the studied people. The level of vaccine hesitancy was 165 (26.5%) and vaccine acceptance was 457 (73.5%). The main reason for willingness to take the vaccine was to protect oneself from COVID-19 disease, 364 (58.5%) and for unwillingness it was fear of vaccine, 154 (24.8%). Mass media was the main source of information about the vaccine, 472 (75.9%). Age (adjusted odds ratio (AOR): 2.1, 95% CI: 1.2-3.7), religion (AOR: 2.6, 95% CI: 1.1-5.9), history of COVID-19 disease (AOR: 4.6, 95% CI: 1.4-14.9), knowledge related to COVID-19 vaccine (AOR: 1.9, 95% CI: 1.2-3.1) and attitude towards COVID-19 vaccine (AOR: 13.2, 95% CI: 8.3-20.9) were factors associated with vaccine hesitancy. Conclusion: Low proportion of COVID-19 vaccine hesitancy was observed among our study participants. Improving people awareness could help to improve the vaccine acceptance. Focusing of the interventions on the identified risk factors of vaccine hesitancy is important.